Uncertainty avoidance moderates the relationship between transformational leadership and innovation: A meta-analysis - Watts, Logan L; Steele, Logan M; Den Hartog, Deanne N (Journal of International Business Studies, 2020)
Transformational leadership is commonly assumed to facilitate employee innovation in all cultures. Drawing upon field studies from 17 countries, this meta-analysis revealed that supervisor transformational leadership is positively related to individual- and team-level innovation regardless of national boundaries. However, the relationship trended somewhat more strongly in countries with higher levels of uncertainty avoidance. These findings suggest that employee innovation in most countries can be enhanced by investing in supervisor transformational leadership, but organizations operating in countries with higher levels of uncertainty avoidance may benefit more from this strategy.